Prevalence and incidence estimates for syphilis, chlamydia, gonorrhea, and congenital syphilis in Colombia, 1995-2016 - Eline L. Korenromp; Cielo Ríos; Amparo Liliana Sabogal Apolinar; Sidia Caicedo; Diego Cuellar; Iván Cárdenas; Ricardo Luque Nuñez; Norma Constanza Cuéllar; Martha Ruíz; Adriana Cruz; Hernando Gaitan-Duarte; Carolina Duarte Valderrama; et al. (Pan American Health Organization, 2018)
Objectives. To estimate adult (15-49 years old) prevalence and incidence of active syphilis, gonorrhea, and chlamydia, and incidence of congenital syphilis (CS) and adverse birth outcomes (ABOs) in Colombia, over 1995-2016. Methods. The Spectrum-STI epidemiological model tool estimated gonorrhea and chlamydia prevalences as moving averages across prevalences observed in representative general population surveys. For adult syphilis, Spectrum-STI applied segmented polynomial regression through prevalence data from antenatal care (ANC) surveys, routine ANC-based screening, and general population surveys. CS cases and ABOs were estimated from Spectrum's maternal syphilis estimates and proportions of women screened and treated for syphilis, applying World Health Organization case definitions and risk probabilities. Results. The Spectrum model estimated prevalences in 2016 of 0.70% (95% confidence interval (CI): 0.15%-1.9%) in women and 0.60% (0.1%-1.9%) in men for gonorrhea and of 9.2% (4.4%-15.4%) in women and 7.4% (3.5%-14.7%) in men for chlamydia, without evidence for trends over 1995-2016. The prevalence of active syphilis in 2016 was 1.25% (1.22-1.29%) in women and 1.25% (1.1%-1.4%) in men, decreasing from 2.6% (2.1%-3.2%) in women in 1995. Corresponding CS cases in 2016 (including cases without clinical symptoms) totaled 3 851, of which 2 245 were ABOs. Annual CS and ABO estimates decreased over 2008-2016, reflecting decreasing maternal prevalence and increasing cases averted through ANC-based screening and treatment. Conclusions. The available surveillance and monitoring data synthesized in Spectrum-STI- and the resulting first-ever national STI estimates for Colombia-highlighted Colombia's persistently high STI burden. Adult syphilis and congenital syphilis are estimated to be falling, reflecting improving screening efforts. Strengthened surveillance, including with periodic screening in low-risk populations and future refined Spectrum estimations, should support planning and implementation of STI prevention and control, including CS elimination.